PEMBELAJARAN BERPARADIGMA AL-QURâ€™AN UNTUK MENGATASI KESULITAN SISWA MADRASAH DALAM MEMPELAJARI MATEMATIKA - Abdussakir, Abdussakir (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2008)
We have known, mathematic is considered the difficult lesson by several students. The student mathematic achievement is very lack of satisfactory and very less, moreover madrasahâ€™s student. This article wants to offer the newest way to up grade the studentâ€™s mathematic achievement. The mathematic learning should be performed by a heart, not only by a brain. This is a scientist concept at Koran who can use â€œfikirâ€ and â€œdzikirâ€, a heart and a brain, â€œbayaniâ€, â€œburhaniâ€ and â€œirfaniâ€ method in mathematic learning. In other word, the mathematic learning should be involved the intellectual questions (IQ), spiritual questions (SQ), and emotional questions (EQ).Keyword: Paradigm, Matematic, al-Quran